Designing a new EU-Turkey strategic gas partnership - Simone Tagliapietra; Georg Zachmann (Bruegel, 2015)
The European Commission's February 2015 Energy Union Communication calls for intensified work on the Southern Gas Corridor (SGC) and the establishment of a new strategic energy partnership with Turkey. The presence of the European Union and Turkey in the region is complementary in a number of ways. Building on this could unlock the region's gas export potential and make gas supplies to the EU and Turkey more secure. The EU should establish dedicated energy diplomacy taskforces with Turkey and each potential supplier in the region (Azerbaijan, Turkmenistan, Iran, Kurdistan Region of Iraq). This would allow the EU and Turkey to make use of their complementary diplomatic leverages to overcome barriers to regional gas trade. In parallel, the EU should establish with Turkey a dedicated financing mechanism to facilitate gas infrastructure investments, with a primary focus on the upgrade of the Turkish gas grid. The European Investment Bank might play a role in attracting private and institutional investors through its financing tools. The four "EU-Turkey Energy Diplomacy Taskforces" and the "EU-Turkey Gas Infrastructure Financing Initiative" would be initiatives of the recently started EU-Turkey Strategic High Level Energy Dialogue.
Keywords: 330